Characterization of a loss-of-function NSF attachment protein beta mutation in monozygotic triplets affected with epilepsy and autism using cortical neurons from proband-derived and CRISPR-corrected induced pluripotent stem cell lines - Ali, Gowher; Shin, Kyung Chul; Habbab, Wesal; Alkhadairi, Ghaneya; AbdelAleem, Alice; AlShaban, Fouad A.; Park, Yongsoo; Stanton, Lawrence W. (Frontiers in Neuroscience, 2024)
We investigated whether a homozygous recessive genetic variant of NSF attachment protein beta (NAPB) gene inherited by monozygotic triplets contributed to their phenotype of early-onset epilepsy and autism. Induced pluripotent stem cell (iPSC) lines were generated from all three probands and both parents. The NAPB genetic variation was corrected in iPSC lines from two probands by CRISPR/Cas9 gene editing. Cortical neurons were produced by directed, in vitro differentiation from all iPSC lines. These cell line-derived neurons enabled us to determine that the genetic variation in the probands causes exon skipping and complete absence of NAPB protein. Electrophysiological and transcriptomic comparisons of cortical neurons derived from parents and probands cell lines indicate that loss of NAPB function contributes to alterations in neuronal functions and likely contributed to the impaired neurodevelopment of the triplets.